Immobilization of lipases on glyoxyl–octyl supports: Improved stability and reactivation strategies. Issue 8 (August 2015) - Suescun, Angélica; Rueda, Nazzoly; dos Santos, Jose C.S.; Castillo, John J.; Ortiz, Claudia; Torres, Rodrigo; Barbosa, Oveimar; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: CRL and CALA have been immobilized on octyl–glyoxyl supports. The immobilization produced a hyperactivation of both enzymes. After incubation at pH 10 covalent bonds are established. Enzyme stability increase after covalent binding. OCCLX-CALA may be reactivated by unfolding/refolding strategies. Abstract: Lipases from Candida rugosa (CRL) and from Candida antarctica (isoform A) (CALA) have been successfully immobilized on octyl–glyoxyl agarose (OCGLX) beads and compared to the octyl–agarose (OC) or glyoxyl (GLX) beads immobilized counterparts. Immobilization on OCGLX gave similar hyperactivations than those found for the immobilization on OC supports, although the incubation at pH 10.0 for 4 h decreased the activity of both enzymes by 25%. After reduction, more than 95% of the enzyme activity was covalently attached to the support. The fraction not covalently attached was desorbed by washing with detergent. These biocatalysts were more stable than the octyl counterparts in thermal or organic solvent inactivation. More interestingly, the irreversible immobilization permitted the reactivation of CALA biocatalysts inactivated by incubation in organic solvent, after unfolding in the presence of guanidine and refolding in aqueous buffer (around 55% of the activity could be recovered during 3 successive cycles of inactivation/reactivation). GLX–CALA permitted to recover 75% of the activity, but the thermal stability and activity was much lower, and this strategy could not be applied to CRL. Neither the enzyme immobilized on cyanogen bromide nor the enzyme immobilized on OCGLX exhibited significant activity after the unfolding/refolding strategy.